2012
DOI: 10.1177/1479972312464244
|View full text |Cite
|
Sign up to set email alerts
|

Volitional pursed lips breathing in patients with stable chronic obstructive pulmonary disease improves exercise capacity

Abstract: Pursed lips breathing (PLB) is used by a proportion of patients with chronic obstructive pulmonary disease (COPD) to alleviate dyspnea. It is also commonly used in pulmonary rehabilitation. Data to support its use in patients who do not spontaneously adopt PLB are limited. We performed this study to assess the acute effects of PLB on exercise capacity in nonspontaneously PLB patients with stable COPD. We performed a randomized crossover study comparing 6-min walk test (6MWT) at baseline without PLB with 6WMT u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 19 publications
1
32
0
1
Order By: Relevance
“…Randomisierte, kontrollierte Studien zum Stellenwert der physiotherapeutischen Atemtherapie oder zum Nutzen der einzelnen physiotherapeutischen Atemtechniken in der Behandlung der COPD sind in sehr geringem Maße verfügbar. Randomisierte Studien [269,270], eine systematische Übersicht [271], sowie eine Evaluation der Evidenz aus systematischen Übersichten [272] zeigen positive Effekte von Atemtechniken, insbesondere der dosierten Lippenbremse, aber auch von einem Training der Zwerchfellatmung, das in Übereinstimmung mit den BTS-Empfehlungen zur physiotherapeutischen Atemtherapie Patienten mit COPD von Atemtechniken profitieren. Weniger gut belegt sind atemerleichternde Körperpositionen wie das Sitzen mit nach vorne geneigtem Oberkörper, die Fixation des Schultergürtels oder Relaxationsübungen, die bei COPD-Patienten mit Angst und ausgeprägter Dyspnoe zur Reduktion von Dyspnoe und der Atemfrequenz führen können.…”
Section: Physiotherapeutische Atemtherapieunclassified
“…Randomisierte, kontrollierte Studien zum Stellenwert der physiotherapeutischen Atemtherapie oder zum Nutzen der einzelnen physiotherapeutischen Atemtechniken in der Behandlung der COPD sind in sehr geringem Maße verfügbar. Randomisierte Studien [269,270], eine systematische Übersicht [271], sowie eine Evaluation der Evidenz aus systematischen Übersichten [272] zeigen positive Effekte von Atemtechniken, insbesondere der dosierten Lippenbremse, aber auch von einem Training der Zwerchfellatmung, das in Übereinstimmung mit den BTS-Empfehlungen zur physiotherapeutischen Atemtherapie Patienten mit COPD von Atemtechniken profitieren. Weniger gut belegt sind atemerleichternde Körperpositionen wie das Sitzen mit nach vorne geneigtem Oberkörper, die Fixation des Schultergürtels oder Relaxationsübungen, die bei COPD-Patienten mit Angst und ausgeprägter Dyspnoe zur Reduktion von Dyspnoe und der Atemfrequenz führen können.…”
Section: Physiotherapeutische Atemtherapieunclassified
“…The subgroup analysis for the outcome of the 6WMT showed that the effect of walking for elderly people with COPD was inconsistent with findings fromBhatt, Luqman-Arafath, and Gupta (2013), which may be related to the clinical heterogeneity and the frequency, time, and intensity of walking. The evidence did not demonstrate that rehabilitation programs improve SaO 2 in elderly COPD patients, perhaps because of small sample sizes of the trials and the lack of detailed data.The innovation of this paper is that we conducted a systematic review and meta-analysis of data related to elderly patients with COPD who participated in pulmonary rehabilitation programs.…”
mentioning
confidence: 69%
“…Recently, Bhatt et al 15 reported good results regarding exercise tolerance improvement in patients with severe COPD. They conducted a crossover trial investigating the effects of PLB on 6MWD and found that patients walked 34.9 m more if they breathed with volitional PLB, compared to breathing normally (P=.002), with a concomitant reduction in RR after the test.…”
Section: Discussionmentioning
confidence: 99%
“…Patients may present increased residual volume at rest (static hyperinflation) and/or may develop hyperinflation under strain (dynamic hyperinflation), as the increase of the respiratory rate shortens the expiratory time. 15 In COPD patients, some studies investigated the effects of PEP on strength, endurance, lung volumes or walking exercise. The equal pressure point (EPP) is shifted peripherally, resulting in an earlier closure of the peripheral airways with consequent air trapping.…”
Section: Introductionmentioning
confidence: 99%